Tau in the Pathophysiology of Parkinson’s Disease - Pan, Lina; Meng, Lanxia; He, Mingyang; Zhang, Zhentao (Journal of molecular neuroscience, 2021)
The pathological hallmarks of Parkinson's disease (PD) are the progressive loss of dopaminergic neurons in the substantia nigra and the formation of Lewy bodies (LBs) in remaining neurons. LBs primarily consist of aggregated α-Synuclein (α-Syn). However, accumulating evidence suggests that Tau, which is associated with tauopathies such as Alzheimer’s disease (AD), progressive supranuclear palsy (PSP), and argyrophilic grain disease, is also involved in the pathophysiology of PD. A genome-wide association study (GWAS) identified MAPT , the gene encoding the Tau protein, as a risk gene for PD. Autopsy of PD patients also revealed the colocalization of Tau and α-Syn in LBs. Experimental evidence has shown that Tau interacts with α-Syn and influences the pathology of α-Syn in PD. In this review, we discuss the structure and function of Tau and provide a summary of the current evidence supporting Tau’s involvement as either an active or passive element in the pathophysiology of PD, which may provide novel targets for the early diagnosis and treatment of PD.